“One’s Own Body of Pure Channels and Elements”: The Teaching and Practice of Tibetan Yoga at Namdroling - Worth, Naomi (Religions, 2021)
The Tibetan yoga practice known as “winds, channels, and inner heat” (rtsa rlung gtum mo) is physically challenging, and yet is intentionally designed to transform the mind. This chapter explores the relationship between Buddhist doctrine and this physical practice aimed at enlightenment through the teachings of a contemporary yoga master at Namdroling Tibetan Buddhist Monastery and Nunnery in Bylakuppe, Karnataka, South India. This ethnographic profile exemplifies the role of a modern Tibetan lama who teaches a postural yoga practice and interprets the text and techniques for practitioners. While many modern postural yoga systems are divorced from religious doctrine, Tibetan Buddhist yoga is not. This essay highlights three key areas of Buddhist doctrine support the practice of Sky Dharma (gNam chos) yoga at Namdroling: (1) The history and legacy that accompany the practice, which identify the deity of Tibetan yoga as a wrathful form of Avalokiteśvara, the Buddha of compassion; (2) The role of deity yoga in the practice of Tibetan yoga, where the practitioner arises as the deity during yoga practice, an all-consuming inner contemplation; and (3) The framing of Tibetan yoga within the wider philosophy of karma theory and its relationship to Buddhist cosmology. Practitioners of Tibetan yoga endeavor to burn up karmic seeds that fuel the cycle of rebirth in the six realms of saṃsāra. In Tibetan yoga, the body acts in service of the text, the philosophy, and the mind to increasingly link the logic of texts to experience in meaningful ways.